Endocuff-assisted colonoscopy: a new accessory to improve adenoma detection rate? Technical aspects and first clinical experiences - Lenze, Frank; Beyna, Torsten; Lenz, Philipp; Heinzow, Hauke S.; Hengst, Karin; Ullerich, Hansjoerg (Endoscopy, 2014)
Background and study aims: The Endocuff is a new colonoscopy accessory that has been designed to improve both the adenoma detection rate and endoscope tip control. Patients and methods: A total of 50 Endocuff-assisted colonoscopies were analyzed retrospectively with regard to safety, procedural success, and complications.Results: The cecal intubation rate was 98 %, and the mean intubation time was 6.0 minutes (95 % confidence interval 5.3 – 6.6 minutes). The ileal intubation rate was 76 %. In 30 % of patients, the Endocuff caused small, superficial, “scratch-like” mucosal lesions. In all other patients, no Endocuff-associated complications were observed. A total of 36 adenomas were detected in 50 patients. The adenoma detection rate was 34 %.Conclusions: Endocuff-assisted colonoscopy showed good procedural success rates in terms of cecal intubation rate and time, and a promising adenoma detection rate. Endocuff seems to improve endoscope tip control, especially during polypectomy. Endocuff may be a useful device for colorectal adenoma screening, and should be investigated in larger trials.